Complications of robotic delineation of oil spills at sea - Hwang, J; Neil Bose; Fan, S; Robinson, B; Kiril Tenekedjiev (2019)
Disasters at sea often run the risk of producing oil spillage. The level of spill depends on the type of vessel, the severity of damage, the weather conditions and nature of the disaster. Rapid response is crucial, yet an effective response depends on knowledge of the extent of the spill response instruments for delineation of an oil spillage at sea. Three sensors were tested to sense marine through the water column. Autonomous underwater vehicles are attractive to delineate a spill due to their capability of rapid deployment and ability to sense in three-dimensional space. This paper describes the assessment of oil sensors for their effectiveness on A UV s as rapid diesel oil in regular and breaking wave conditions. The outcomes implied that the robotic mission algorithms must account for oil in water that forms patches and clouds of droplets of various sizes and distribution at varied depths using appropriate sensors.